Development of Educational Media For Distribution Network Practicum Using A Lora-Based Load Monitoring and Control Tool - Andi Wawan Indrawan; Hamsu Abdul Gani; Ruslan (Indonesian Journal Publisher, 2026)
This study aims to develop and evaluate innovative learning media for the low-voltage distribution network load imbalance practicum using LoRa-based monitoring and control tools. Adopting a Research and Development (R&D) design with the ADDIE model, this study will be at the Ujung Pandang State Polytechnic (PNUP) in 2023. The research methodology involves five stages of ADDIE (Analysis, Design, Development, Implementation, Evaluation) to develop learning media in the form of Semester Learning Plans (RPS), modules, jobsheets, and tool guides. Validation by two experts was used to measure the feasibility of the product, while practicality was assessed through questionnaires in small (N=7) and large (N=38) group trials. Sensor accuracy testing showed a very low error rate (0.15% - 0.53%) compared to standard measuring instruments, proving the reliability of the device. Effectiveness was measured through pre-test and post-test in 38 experimental students and 38 control class students, analyzed by Kolmogorov-Smirnov, Levene, and paired sample t-test. The results of the study showed that the learning media and its supporting devices obtained the category of